Interrelationship between team cohesion, coaching environment, need satisfaction, and wellbeing in hockey players - Merrett, C. K.; Duda, J. L. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
In their work involving basketball players and grounded in Basic Needs Theory (BNT; Deci & Ryan, 2002), Blanchard and colleagues (Blanchard, Amiot, Perrault, & Vallerand, 2009) found perceived team cohesion to positively predict players` basic need satisfaction, which in turn, predicted greater satisfaction in basketball and positive emotions. A perceived controlling coach climate negatively impacted on feelings of autonomy. Extending their work, this study considered both controlling and autonomy-supportive features of the coachcreated environment and distinguished between task- and social cohesion. Further, both positive and negative indicators of athletes` well-being were taken into account. The interplay between the variables was examined in both an elite and recreational sample of hockey players. More specifically, the present research: i) determined the links between player perceptions of task and social cohesion, the coaching climate (both controlling and autonomy-supportive features), BN satisfaction, and reported indicators of well-being (i.e, subjective vitality) and ill-being (i.e., emotional and physical exhaustion), and ii) as assumed in BNT, tested for invariance in these relationships between elite and non-elite hockey players. Method Elite and non-elite (school/club level) (M age =17.59 years) field hockey players completed a multi-scale questionnaire pack assessing the targeted variables. Results Structural equation modeling supported the hypothesized models for elite (CFI= .91, TLI= .90, RMSEA= .06, Chi-squared= 1209.8, df 606 p< .01) and non-elite (CFI= .90, TLI= .90, RMSEA= .07, Chi-squared= 1184.1, df 606, p< .01) hockey player samples. The overall hypothesized structural models were invariant albeit some specific paths between variables were significantly different between elite and non-elite models. Most notably the paths between social cohesion and the three basic needs were variable between the two models. Discussion Findings support the assumed universality of BNT across elite and non-elite hockey samples but highlights variance in specific relationships between variables within the BNT framework. The theoretical and applied implications of these results are discussed.